Transformasi Pariwisata Gunung Kemukus: Studi Upaya Pemerintah Daerah dalam Meningkatkan Citra Positif - Destariyadi, Ramadhan Ekagandhi; Sriyanto, Agus (Academic Journal of Da'wa and Communication, 2024)
Mount Kemukus was once famous as a place for ritual tourism and wealth “ngalap berkah”, but now it has become a religious and family tourism with interesting photo spots and is increasingly crowded. This is inseparable from the role of the Sragen Youth, Sports and Tourism Office. The purpose of this study is to describe the Image of Mount Kemukus by the Sragen Youth, Sports and Tourism Office as a Religious and Family Tourism. The research method used is qualitative descriptive. Data was collected through documentation, observation, and interviews with selected sources. The results of the study refer to Rosady Ruslan's PR Programming and Communication theory showing that the image of Mount Kemukus by the Sragen Diaspora is carried out by continuing to produce positive events and programs that receive support, urgency, and ideas, disseminated through conventional media, the web, and IG @disporasrg. The Sragen Dispora also carried out an overall evaluation of various programs to monitor Mount Kemukus's image, MSMEs, and homestays. This image has a positive impact on public trust and the image of Mount Kemukus.